STRATEGI GURU MADRASAH DALAM MENGHADAPI PERKEMBANGAN TEKNOLOGI GENERATIVE AI (GenAI) UNTUK MEWUJUDKAN SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Divo, Divo Miraj; Bambang Sumarsono, Raden; Aprillia RD, Zabrina (Satya Widya, 2025)
The role of madrasah teachers is crucial in guiding students to achieve quality learning. In the digital era, technological developments, particularly artificial intelligence (AI) such as ChatGPT, have had a significant impact on education. While ChatGPT can positively contribute to the teaching and learning process, it also poses new challenges in the form of declining interest in literacy, reduced critical thinking skills, and an increased risk of academic plagiarism. Therefore, madrasah teachers' strategies in anticipating the negative impacts of technology are urgently needed for research. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation conducted at Madrasah Aliyah Negeri 2 Malang City. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results show that madrasah teachers implement various preventive strategies, such as multiliteracy-based pedagogical planning, the implementation of open-ended question-based assessments, and the use of AI-based writing detectors. The discussion of this research elaborates on these strategies by linking them to literacy theory, constructivism, and previous literature reviews. The findings of this study confirm that madrasah teachers' strategies have a significant contribution to efforts to achieve the Sustainable Development Goals (SDGs), especially goal 4 regarding quality education.